2016
DOI: 10.1017/s136672891600078x
|View full text |Cite
|
Sign up to set email alerts
|

“I Readed the Book Last Week.” The Role of Dominant Language, Receptive Vocabulary and Language Structure on Morphosyntactic Awareness in Monolingual and Heritage Language Children

Abstract: In this research, 5- and 6-year-old monolingual (English) and heritage language (English–Spanish, English–Urdu) children completed a grammaticality judgment test to assess their awareness of grammatically correct and incorrect morphosyntactic structures in English. Results demonstrated that language group differences were minimized when heritage language children exhibited average receptive vocabulary proficiency for the sample, and when more difficult morphosyntactic structures were assessed. In this middle r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 49 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…Past research, however, has shown inconsistent findings with regard to monolingualbilingual differences on measures of syntactic awareness. Some studies have shown bilingual advantages (e.g., Bialystok, 2007;Cromdal, 1999;Davidson et al, 2010), whereas other studies have shown bilingual advantages for only certain groups of bilingual children (i.e., highly proficient bilinguals: Davidson et al, 2017). In contrast, additional studies have shown that bilingual children perform more poorly than monolingual children (e.g., Da Fontoura & Siegel, 1995;Lipka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Past research, however, has shown inconsistent findings with regard to monolingualbilingual differences on measures of syntactic awareness. Some studies have shown bilingual advantages (e.g., Bialystok, 2007;Cromdal, 1999;Davidson et al, 2010), whereas other studies have shown bilingual advantages for only certain groups of bilingual children (i.e., highly proficient bilinguals: Davidson et al, 2017). In contrast, additional studies have shown that bilingual children perform more poorly than monolingual children (e.g., Da Fontoura & Siegel, 1995;Lipka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, additional studies have shown that bilingual children perform more poorly than monolingual children (e.g., Da Fontoura & Siegel, 1995;Lipka et al, 2005). A number of reasons have been postulated to explain these inconsistencies in findings, including the possibility that fewer monolingual-bilingual differences are found when bilingual children are tested in their dominant language and show sufficient levels of receptive vocabulary ability in that language (Davidson et al, 2010(Davidson et al, , 2017. The present study suggests that an even more complicated picture may exist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations